Theobromine for the treatment of persistent cough: a randomised, multicentre, double-blind, placebo-controlled clinical trial - Morice, Alyn H.; McGarvey, Lorcan; Pavord, Ian D.; Higgins, Bernard; Chung, Kian Fan; Birring, Surinder S. (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
Background: To investigate the effect of BC1036 on health-related quality of life (QOL) in subjects with persistent cough. The secondary objective was to investigate the effect of BC1036 on subjective cough severity. Methods: This was a randomised, multicentre, double-blind, placebo-controlled, parallel-group study in 289 subjects with persistent cough. Subjects received BC1036 or placebo twice daily for 14 days. The primary endpoint comprised cough-related QOL assessed using the validated Leicester Cough Questionnaire (LCQ) at Day 14. Secondary endpoints comprised the LCQ scores at Day 7 and Day 28, cough severity VAS scores at each visit and pulmonary function tests. Results: At baseline, mean total LCQ score in the BC1036 group was lower (i.e., worse QOL) than placebo (P